The Effect of the Exposure into a low dose of X-ray on human Hematological Parameters - Jalal, Deena; Al- Attab, Hadi; Hayder Ali Hussein Al mansarawi (University of Thi-Qar Journal of Science, 2024)
Although low dose of X-rays are widely used in medical radiology, the harmful effects of exposure to low dose of X-rays during diagnostic radiological examination is still a commonly discussed topic. Objective of the current study was to investigate the effects of exposing low dose of X-rays on human parameters, like the white blood cell (WBC), red blood (RBC), hemoglobin (HGB), and platelet counts (PLT) . znn We exposed a human blood into 60kv and 100mA for 80ms of medical diagnostic X-rays. Non-irradiated cells represented as the control group. The results showed there are no changes in the percentage in the RBC , WBC ,PLT , and HGB that were exposed to low dose X-rays, comparing to the corresponding non-irradiated blood cells, control samples, at all the harvest time-points. These finding suggested that there were no harmful effects of the diagnostic low dose X-rays in an in vitro exposure of RBC, WBC , PLT , and HGB.